Recent experience on atrial septal defect device closure at Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani; Shrestha, Manish; Bogati, Amrit; Dhungel, Sachin; Acharya, Kiran; Shakya, Urmila; Sharma, Poonam; Aryal, Shilpa; Adhikari, Jagat; Malla, Rabi (Nepalese Heart Journal, 2019)
Background and Aims: Atrial septal defect (ASD) device closure has been accepted worldwide as an alternative to surgical closure with the excellent results. This interventional, non-surgical technique plays an important role in the treatment of ASD. This audit aims to report our experience of ASD device closure in our centre. Methods: This cross sectional study was conducted at Shahid Gangalal National Heart Centre, Kathmandu, Nepal. All patients who were attempted for ASD device closure from February 2016 to January 2018 were included. ASD size, device size, procedural approach, and device implantation success rates were retrospectively analyzed from our hospital records. Result: During the study period, 566 cases were attempted for device closure. Among them device was successfully implanted in 557(98.4% of cases). In nine cases ASD device could not be implanted. Among the 557 successful cases, 401 (71.9%) were female. Age ranged from 5 to 72 years with the mean of 30.9 years. In five patients, transcatheter closure cases, was done under general anesthesia with the guidance of transesophgeal echocardiogram. In all other patients, device closure was done in local anesthesia under transthoracic echocardiography guidance. ASD size ranged from 7mm to 37mm with the mean of 20.8mm. ASD device ranged from 8 to 42mm with the mean of 26.5mm. Four different devices were used with the Amplatzer septal occluder used in 527 (94.6%) patients, hyperion( Comed) device in 10 (1.7%) patients, Memopart (Lepu) device in 19 (3.4%) patients and Cera (Life tech) device in 1(0.1%) patients. Discussion: ASD device closure is a safe and effective procedure.